Interference of sulfur with shoot accumulation and toxic effects of selenium in wheat - Yazici, A; Torun, B; Ozturk, L; Cakmak, I (MTT, 2005)
Six bread wheat (Triticum aestivum) cultivars were grown under greenhouse conditions to study the role of increasing sulfur (S) application (0, 75 and 225 mg S kg-1 soil) on dry matter production, shoot accumulation of selenium (Se) and development of Se toxicity symptoms. Plants were grown for 3 weeks in greenhouse under different Se (0, 0.2, 1 and 5 mg Se kg-1 soil) and S treatments which were applied in forms of sodium selenate and CaSO4, respectively. As the genoypic differences found for sensitivity to Se toxicity and Se accumulation in shoot were relatively small, the results obtained are presented as average of all cultivars. At the nil Se, growing plants without S application did not affect dry matter production of plants compared to the plants treated with increasing S application, indicating that the S status of the soil used in the experiments was not limited to plant growth. Increasing Se application to soil from 0 to 5 mg kg-1 significantly reduced plant dry matter production only at the low S applications. As average of all cultivars, decreasing Se supply from 5 to 0 mg kg-1 increased plant dry matter production 11-fold at the nil S treatment and only 1.2-fold at the a 225 mg kg-1 S treatment. When plants were grown at the highest Se application without S, very severe toxicity symptoms, such as whitish and chlorotic patches, developed on the older leaves, mainly on the leaf basis. The leaf parts affected particularly by Se toxicity were whitish and had an albino appearance, lacking chlorophyll. Application of S prevented development of these leaf symptoms. Severity of Se toxicity symptoms on leaves were not directly related to the tissue concentration of Se and greatly affected from the concentrations of S in leaves. In Streated plants containing 398 mg Se per kg dry weight of leaves there was no or slight Se toxicity symptoms on leaves, while in plants with 213 mg Se per kg dry weight of leaves, but without S treatment, leaf symptoms were very severe, and there were marked decreases in dry matter production. This indicates importance of Se/S ratio in the tissue in development of Se injury in plants. Sulfur application caused marked decreases in Se concentration of plants. Increase in S application from 0 to 225 mg kg-1 reduced Se concentration of plants from 28 to 3 mg kg-1 at the Se rate of 0.2 mg kg-1, from 213 to 22 at the Se rate of 1 mg kg-1 and from 1542 to 398 mg kg-1 at the Se rate of 5 mg kg-1. By contrast, increasing Se applications generally increased S concentration of plants, in most cases by 2-fold. This increasing effect of Se on S accumulation was more pronounced in the case of total amount of Se per plant (S content). The results obtained indicate that the toxic effects of Se in wheat plants can be markedly minimized by increasing S applications. Sulfur is highly effective in repressing uptake of Se by roots. Sulfur is also affective to interfere with the toxic actions of Se at cellular level. Therefore, the critical toxic Se concentrations in leaves are much greater in plants containing lower than the plants with higher S concentrations. In contrast to the S-induced decrease in Se uptake, increasing Se application stimulated S uptake of plants. It seems very likely that there is a common uptake system (sulphate transporter?) mediating uptake and transport of Se and S in wheat. The stimulating effect of Se on accumulation of S in plants suggests that Se possibly interferes with the action of sulphate to repress the activity of sulphate transporter.
Keywords: Ka; wheat; selenium; sulphur